Achieving Social Entrepreneurship Sustainability through the Development of Human Resource Business Partner Competency - Pradipta, Bernadinne Cintantya; Sugiarto, Agus (Universitas Proklamasi 45, 2024)
Building a sustainable business is the top priority of all business actors. The easiest way to accomplish this is to start a business based on social entrepreneurship, which primarily focuses on developing human resource (HR) business partner competency. This study aims to identify reasons for the need to develop the HR business partner competency with a social entrepreneurship concept and the challenges experienced by IKAT Indonesia in the weaving industry. A case study approach was employed with multiple informants who had relevant experience and knowledge. The results show that the reasons included the need to improve business partners’ motives, traits, self-image, knowledge, and skills. The development of HR business partner competency with the social entrepreneurship concept was implemented by using several methods, including projects, workshops, and coaching and mentoring. Further, the challenges faced consisted of limited access, education, and motivation, and the younger generation’s lack of interest in maintaining woven crafts. These findings are expected to be used as references in social entrepreneurship-based business sustainability, particularly in terms of developing the HR business partner competency.